The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11837-020-04404-0
|View full text |Cite
|
Sign up to set email alerts
|

Damage Analysis in Dual-Phase Steel Using Deep Learning: Transfer from Uniaxial to Biaxial Straining Conditions by Image Data Augmentation

Abstract: Microstructural damage can occur during metal forming, but how and where this happens vary with the local microstructure and strain path. Large-scale analysis of such damage mechanisms is particularly important in advanced steels with a heterogeneous phase distribution. In our previous work, we demonstrated that deep learning enables a mechanism-based, statistical analysis by classifying many individual damage sites. The aim of this work is to generalize this approach to different stress states, e.g., biaxial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the calibration process, the modeling method did not need to identify the joint zero error separately, which simplified the calculation and improved the calibration efficiency. At the same time, the method also overcame the singularity problem in the traditional D-H model [5]. Yang et al found that mirror therapy had a significant effect on patients with nerve injury and poor motor function [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the calibration process, the modeling method did not need to identify the joint zero error separately, which simplified the calculation and improved the calibration efficiency. At the same time, the method also overcame the singularity problem in the traditional D-H model [5]. Yang et al found that mirror therapy had a significant effect on patients with nerve injury and poor motor function [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The spatial resolution of the obtained images was 32.5 nm/pixel. The high resolution electron microscopic images of the microstructure were segmented using deep learning based convolutional neural networks [4] developed with Tensorflow 2.0.0. For this purpose, the panoramic images were cropped to smaller window sizes of 512 * 512 pixels.…”
Section: Input Data: Segmented Microstructure Phase Mapsmentioning
confidence: 99%
“…In this context, deformation induced damage sites can be detected and subsequently classified with respect to their appearance, as shown by Kusche et al and Medghalchi et al for damage sites in dual-phase steel. [34,35] In this study, we explore the prevalent mechanisms of codeformation and their dependence on strain and rate in a Mg-Ca(Mg,Al) 2 metallic-intermetallic composite microstructure. To this end, we use micromechanical testing and scanning electron microscopy, coupled with automated image analysis to identify and quantify the dominant damage mechanisms of brittle failure in the intermetallic, and interfacial decohesion at the internal interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, deformation induced damage sites can be detected and subsequently classified with respect to their appearance, as shown by Kusche et al and Medghalchi et al for damage sites in dual‐phase steel. [ 34,35 ]…”
Section: Introductionmentioning
confidence: 99%